First record of the invasive algae Didymosphenia geminata in the Lake Nahuel Huapi: Argentina, Patagonia - Beamud, Sara Guadalupe (2013)
The benthic diatom Didymosphenia geminata (L yngbye) M. Schmidt is a ver y aggressive invasive species found in riversand streams in different parts of the world. It has become a major concern for its tendency to form conspicuous blooms in oligotrophic aquatic systems with potential for detrimental impacts on recreational fi shing. Given its explosive development and the notable appearance in Lake Nahuel Huapi during the austral summer of 2013, our aim was to document the fi rst record for a large (557 km 2 ) lentic waterbody in the Andean Patagonia region.